Relationship between Knowledge and Attitude with Tuberculosis Prevention Efforts in Preclinical Students - Lumbantobing, Romauli; Oktavia, Lamtiur; Djojosaputro, Mulyadi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tuberculosis (TB) is an infectious disease that can be transmitted, caused by the bacteria Mycobacterium tuberculosis. It is still one of the health problems for national and global communities. This disease can cause disability and even death for sufferers, so it becomes a focus in the goals of sustainable health development. Objective to analyze the relationship between knowledge and attitudes with tuberculosis prevention efforts in preclinical students of the 2022 intake at the Faculty of Medicine, Indonesian Christian University. Method: This study used analytical research with a cross-sectional approach. The number of samples used was 115 respondents, which were taken using the total sampling technique. Based on the research results, 95.6% of preclinical students of the 2022 batch at the UKI Medical Faculty have good knowledge about tuberculosis and 89.6% of students have good attitudes towards efforts to prevent tuberculosis. In the results of the bivariate analysis using the chi-square test, the relationship between knowledge and efforts to prevent tuberculosis was obtained with a p-value of 0.000 (<0.05). In the analysis of the relationship between attitudes and efforts to prevent tuberculosis, a p-value of 0.009 (<0.05) was obtained. From the results of the chi-square test, there was a significant relationship between knowledge and attitudes with efforts to prevent tuberculosis in preclinical students of the 2022 batch at the Faculty of Medicine, Indonesian Christian University. Conclusion: Good knowledge allows students to understand how TB is transmitted, its symptoms, and control strategies. Meanwhile, a positive attitude will form motivation and concern to actively participate in prevention. Therefore, improving these two aspects is an important key in strengthening TB prevention measures among preclinical students.